The Effect of Rinfogroups as a Discussion Media in Student Learning Motivation - Rahardja, Untung; Aini, Qurotul; Khoirunisa, Alfiah (APTISI Transactions on Management (ATM), 2018)
In the current era of globalization, technology management has touched every aspect of human life. The combination of these two factors will become an innovation in the management of education. At Raharja College, the entire academic community has facilities in the form of an official e-mail, namely Information which functions as a communication medium. However, there is no place for discussion management between students and lecturers, so that the discussion process of learning is considered to be ineffective and inefficient because it is still done directly. Therefore, it is necessary to optimize the use of RinfoApps which is used as a discussion medium for online learning. RinfoGroups is one of the Google System features that can be used as a formal media for the online learning discussion management process. By creating a forum called the class mailing list at RinfoGroups, students and lecturers can discuss anytime, students can share about learning material, and lecturers can also monitor the effectiveness of student discussions, this certainly has a significant influence on student learning motivation. Supported by 2 (two) research methods, namely library research and observation methods. The final results of the research that has been achieved are the formation of a discussion media that is easily accessible anywhere and anytime so that the discussion process between students and lecturers becomes more effective and efficient. Keywords: Rinfogroups, Media Communication, Students, Discussion